Pengaruh Zakat Terhadap Peningkatan Kesejahteraan Masyarakat di Indonesia - Hikmal Asril Annaza; Muhammad Hegel Muchtohari; Muhammad Ferdy Hasan; Ali Murtadho Emzaed (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to evaluate the impact of zakat on improving people's welfare in Indonesia. Zakat, as one of the financial instruments in Islam, plays an important role in reducing poverty and improving social welfare through equitable distribution of wealth. The findings of the study indicate that the distribution of zakat has a significant impact on improving the quality of life of beneficiaries, especially in terms of fulfilling basic needs such as education, health, and economic stability. In addition, zakat has also been proven to reduce poverty rates and reduce income disparities in society. The success of zakat is greatly influenced by professionalism in its management, accuracy in distributing to those in need, and transparency of zakat management institutions. These results emphasize the importance of strengthening the zakat management system and cooperation between institutions so that zakat can function optimally as a tool for economic empowerment and equalizing welfare in Indonesia.